Leupaxin promotes hepatic gluconeogenesis and glucose metabolism by coactivation with hepatic nuclear factor 4α - Xiaomin Luo; Fang Liu; Lijun Zhu; Caizhi Liu; Ruhui Shen; Xiaoyin Ding; Yufan Wang; Xiaofang Tang; Yongde Peng; Zhijian Zhang (Molecular Metabolism)
Background: As the primary source of glucose during fasting, hepatic gluconeogenesis is rigorously regulated to maintain euglycemia. Abnormal gluconeogenesis in the liver can lead to hyperglycemia, a key diagnostic marker and the primary pathological contributor to type 2 diabetes (T2D) and metabolic disorders. Hepatic nuclear factor-4 (HNF4α) is an important regulator of gluconeogenesis. In this study, we identify leupaxin (LPXN) as a novel coactivator for HNF4α. Although previous studies have shown that LPXN is highly correlated with cancer types such as B-cell differentiation and hepatocellular carcinoma progression, the role of LPXN in gluconeogenesis remains unknown. Methods: We initially used protein pull-down assays, mass spectrometry and luciferase assays to identify the coactivator that interacts with HNF4α in gluconeogenesis. We further leveraged cell cultures and mouse models to validate the functional importance of molecular pathway during gluconeogenesis by using adenovirus-mediated overexpression and adeno-associated virus shRNA–mediated knockdown both in vivo and ex vivo, such as in ob/db/DIO mice, HepG2 and primary hepatocytes. Following, we used CUT&Tag and chip qPCR to identify the LPXN-mediated mechanisms underlying the observed abnormal gluconeogenesis. Additionally, we assessed the translational relevance of our findings using human liver tissues from both healthy donors and patients with obesity/type 2 diabetes. Results: We found that LPXN interacts with HNF4α to participate in gluconeogenesis. Knockdown of LPXN expression in the liver effectively enhanced glucose metabolism, while its overexpression in the liver effectively inhibited it. Mechanistically, LPXN could translocate into the nucleus and was essential for regulating gluconeogenesis by binding to the PEPCK promoter, which controlled the expression of an enzyme involved in gluconeogenesis, mainly through the Gcg-cAMP-PKA pathway. Additionally, LPXN expression was found to be increased in the livers of patients with steatosis and diabetes, supporting a pathological role of LPXN. Conclusions: Taken together, our study provides evidence that LPXN plays a critical role in modulating hepatic gluconeogenesis, thereby reinforcing the fact that targeting LPXN may be a potential approach for the treatment of diabetes and metabolic disorders.